Of gods, gifts and ghosts - Heng, Terence, 1978- author.
1 online resource
Keywords: How do individuals inscribe their spiritual identities and diasporic ethnicities in the city? Through a series of sociological and photographic essays, Terence Heng maps the various rituals, collectives, individuals and events that characterise Chinese religion practices in Singapore. From spirit mediums to the Hungry Ghost Festival, each chapter engages with the social, the spatial and the ephemeral, and in so doing it will explore the significance and relevance of Chinese religion in a secular nation-state; reveal the strategies and tactics used by diasporic individuals to perform and retain their identities; uncover the importance of flow and fluidity in the making of sacred space; and evidence the value and efficacy of the use of photographs in social research. Of Gods, Gifts and Ghosts is a ground-breaking exploration into the intersections between visual sociology, cultural geography and creative photographic practice. A visual monograph that gives equal importance to image and text, it interrogates the tensions between sacred and profane, official and unofficial, state and individual, physical and spiritual, peeling away the myriad layers of the spiritual imagination.